2011
DOI: 10.1590/s1516-89132011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hela cell lineage response to β radiation from Holmium-166 embedded in ceramic seeds

Abstract: This work studied the effects of β radiation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This technique involves the homogenization of several components, pouring into moulds and then following a specific procedure of gelation, aging, drying and heat treatment (Hench and West 1990). The preparation of seeds (Diniz et al 2017; Valente et al 2011; Nogueira and Campos 2011; Nogueira and de Campos 2012; Nogueira and Campos 2016) and membranes (Nogueira and de Campos 2012) composed of 165 Ho have been reported in the literature. Seeds usually have dimensions ranging from 0.3 to 0.8 mm in diameter and 1.5 to 1.8 mm in length and a density of 2 to 3.7 g/cm 3 (Valente et al 2011; Nogueira and Campos 2011).…”
Section: Intratumoural Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique involves the homogenization of several components, pouring into moulds and then following a specific procedure of gelation, aging, drying and heat treatment (Hench and West 1990). The preparation of seeds (Diniz et al 2017; Valente et al 2011; Nogueira and Campos 2011; Nogueira and de Campos 2012; Nogueira and Campos 2016) and membranes (Nogueira and de Campos 2012) composed of 165 Ho have been reported in the literature. Seeds usually have dimensions ranging from 0.3 to 0.8 mm in diameter and 1.5 to 1.8 mm in length and a density of 2 to 3.7 g/cm 3 (Valente et al 2011; Nogueira and Campos 2011).…”
Section: Intratumoural Applicationsmentioning
confidence: 99%
“…The preparation of seeds (Diniz et al 2017; Valente et al 2011; Nogueira and Campos 2011; Nogueira and de Campos 2012; Nogueira and Campos 2016) and membranes (Nogueira and de Campos 2012) composed of 165 Ho have been reported in the literature. Seeds usually have dimensions ranging from 0.3 to 0.8 mm in diameter and 1.5 to 1.8 mm in length and a density of 2 to 3.7 g/cm 3 (Valente et al 2011; Nogueira and Campos 2011). Holmium concentrations of 20 wt% (Valente et al 2011) up to 30 wt% (Nogueira and Campos 2016) are achieved in these materials and it has been shown that the radionuclides are homogeneously distributed in the seeds matrix (Nogueira and Campos 2011).…”
Section: Intratumoural Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In turn, permanent implants of biodegradable ceramic seeds with Si, Ca and Ho composition have been developed early. [17][18][19][20][21][22] Such seeds have the length of 1.6 mm and 0.5 mm in diameter, with a polymeric resin covering. Permanent breast implants can be produced by the insertion of a set of fine hypodermic needles distributing those small seeds on the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent scientific advances in diagnosis and disease control have not yet been sufficient to provide a cure for cancer, although remission occurs in many cases. 3 Thus, the search for new treatment modalities is still required. [4][5][6] Brachytherapy is an efficient method for cancer treatment, 7 deploying discreet radioactive segments (seeds) in the tumor and generating a high local radiation dose, which is able to eliminate tumor cells while preserving the healthy surrounding tissue.…”
mentioning
confidence: 99%